Environmental and ecotoxicological effects of drugs used for the treatment of COVID 19 - Efrain Merma Chacca, Donal; Maldonado, Ingrid; Vilca, Franz Zirena (Frontiers in Environmental Science, 2022)
Consumption of different pharmaceuticals has increased since the COVID-19 pandemic. Some health institutions worldwide approved the use of drugs such as ivermectin, hydroxychloroquine, azithromycin, dexamethasone, favipiravir, remdesivir, lopinavir-ritonavir, chloroquine, dexamethasone for the treatment of the virus. Once consumed by humans, these compounds are released in urine and faeces, ending up in wastewater and conducted to treatment plants or directly discharged without prior treatment into surface water and soil, with minimum values recorded between 7 ng/L and < 0.08 μg/L for azithromycin and ivermectin respectively, as well as dexamethasone with 0.73 ng/L in surface water and an average of 50–60 ng/L for favipiravir. Their presence has numerous toxicological effects on aquatic and terrestrial species, influencing population decline and altering the growth of organisms. However, the environmental consequences of pharmaceuticals in the environment are poorly known, especially for antivirals studied in this article. This work aims to analyze the presence, treatment and ecotoxicity of drugs used in the pandemic COVID 19, mainly focusing on aquatic and terrestrial ecosystems since that is where they arrive through wastewater. Ecotoxicological effects on flora, fauna and humans are also analyzed. Once there, they persist in the environment causing severe ecological damage, developmental and growth disorders in animals and plants and, in many cases, even the death of species.